Factors predictive of severe Clostridium difficile infection depend on the definition used. (February 2016) - Khanafer, Nagham; Barbut, Frédéric; Eckert, Catherine; Perraud, Michel; Demont, Clarisse; Luxemburger, Christine; Vanhems, Philippe
Abstract: Context: Clostridium difficile infection (CDI) produces a variety of clinical presentations ranging from mild diarrhea to severe infection with fulminant colitis, septic shock, and death. Over the past decade, the emergence of the BI/NAP1/027 strain has been linked to higher prevalence and severity of CDI. The guidelines to treat patients with CDI are currently based on severity factors identified in the literature and on expert opinion and have not been systematically evaluated. Objective: The objective of this study was to identify factors associated with severe CDI defined according to four different severity definitions (Def): the 2010 SHEA/IDSA guidelines (Def1), the 2014 ESCMID guidelines (Def2), complicated CDI at the end of diarrhea (Def3), and our hospital-specific guidelines (white blood cell (WBC) count ≥15 × 10 9 /L, serum creatinine concentration >50% above baseline, pseudomembranous colitis, megacolon, intestinal perforation, or septic shock requiring intensive care unit admission. Methods: A three-year cohort study was conducted in a university hospital in Lyon, France. All hospitalized (≥48 h) patients ≥18 years old, suffering from CDI, and agreeing to participate were included. Patients were followed-up for 60 days after CDI diagnosis. After bivariate regression analyses, factors associated with severe CDI during the course of disease were identified by a multivariate logistic regression. Statistical significance was reached with a two-sided p-value <0.05. Results: 233 CDI patients diagnosed between 2011 and 2014 were included for a mean incidence rate of 2.15 cases/1000 hospitalized patients or 3.16 cases/10, 000 patient days. Mean age was 65.3 years and 52.5% were men. Death occurred in 37 patients (15.9%) within 60 days of diagnosis. Death was related to CDI in 15 patients (40.5%). Frequency of severe CDI ranges from 11.6% to 59.2% depending on the case-definition. Factors independently associated with severe CDI were: age ≥68 years, male gender, renal disease, and serum albumin <30 g/L according to Def1 (n = 106, 45.5%); exposure to antivirals in the previous 4 weeks, renal disease, and blood neutrophils >7, 5 × 10 9 /L in patients with Def2 (n = 138, 59.2%); abdominal pain, serum albumin <30 g/L, and WBC >10 × 10 9 /L according to Def3 (n = 27, 11.6%); age ≥68 years, renal disease, serum albumin <30 g/L, serum lactate dehydrogenase >248 IU/L, and blood neutrophils >7, 5 × 10 9 /L were associated with severe CDI in patients with Def4 (n = 113, 48.5%). Conclusions: Our results indicate that appropriate case definition is needed for characterizing patients at risk of developing severe CDI. Our study suggest that serum albumin and the presence of renal disease, associated with severe CDI in three definitions, may be useful for identifying patients at risk of a poor outcome. Highlights: Albumin level and renal disease may be predictive of severe CDI. Appropriate definition is needed for characterizing patients at risk for severe CDI. European guidelines for severe disease may need to be reevaluated. Factors associate with severe CDI are depending of used definition.